Boosting phagocytosis and anti‐inflammatory phenotype in microglia mediates neuroprotection by PPARγ agonist MDG548 in Parkinson's disease models. (12th July 2018) - Lecca, Daniela; Janda, Elzbieta; Mulas, Giovanna; Diana, Andrea; Martino, Concetta; Angius, Fabrizio; Spolitu, Stefano; Casu, Maria Antonietta; Simbula, Gabriella; Boi, Laura; Batetta, Barbara; Spiga, Saturnino; et al.
Abstract : Background and Purpose: Microglial phenotype and phagocytic activity are deregulated in Parkinson's disease (PD). PPARγ agonists are neuroprotective in experimental PD, but their role in regulating microglial phenotype and phagocytosis has been poorly investigated. We addressed it by using the PPARγ agonist MDG548. Experimental Approach: Murine microglial cell line MMGT12 was stimulated with LPS and/or MDG548, and their effect on phagocytosis of fluorescent microspheres or necrotic neurons was investigated by flow cytometry. Cytokines and markers of microglia phenotype, such as mannose receptor C type 1; MRC1), Ym1 and CD68 were measured byelisa and fluorescent immunohistochemistry. Levels of Beclin‐1, which plays a role in microglial phagocytosis, were measured by Western blotting. In the in vivo MPTP–probenecid (MPTPp) model of PD in mice, MDG548 was tested on motor impairment, nigral neurodegeneration, microglial activation and phenotype. Key Results: In LPS‐stimulated microglia, MDG548 increased phagocytosis of both latex beads and necrotic cells, up‐regulated the expression of MRC1, CD68 and to a lesser extent IL‐10, while blocking the LPS‐induced increase of TNF‐α and iNOS. MDG548 also induced Beclin‐1. Chronic MPTPp treatment in mice down‐regulated MRC1 and TGF‐β and up‐regulated TNF‐α and IL‐1β immunoreactivity in activated CD11b‐positive microglia, causing the death of nigral dopaminergic neurons. MDG548 arrested MPTPp‐induced cell death, enhanced MRC1 and restored cytokine levels. Conclusions and Implications: This study adds a novel mechanism for PPARγ‐mediated neuroprotection in PD and suggests that increasing phagocytic activity and anti‐inflammatory markers may represent an effective disease‐modifying approach.